HUBUNGAN DUKUNGAN KELUARGA DAN KEMANDIRIAN LANSIA DENGAN KONSEP DIRI LANSIA DI KELURAHAN BAMBANKEREP KECAMATAN NGALIYAN KOTA SEMARANG - Ridlawati Romadlani; Tri Nurhidayati; Agustin Syamsianah (Jurnal Keperawatan Komunitas, 2013)
The old people experience physical, cognitif ability, and  psychological decline. Because of the changing or decline, the old people need support from their closest family. The old people physical changing causesinterference on their independence and from all the changing experienced by the old people especially the pshycological changing will influence the old selves concept. The objective of research is to find out the relationship between family’s support and the old people independence using the old people selves concept in Bambankerep sub district Ngaliyan district Semarang city. The type of research used is study corellation. Thepopulation of this research is the old people in Bambankerep sub district as many as 212 old people. Sample as many as 57 respondents using sample taking technique  by choosing the same characteristics with the old people population scope in Bambankerep Sub district. The old people average age is 67,56 years. 57 respondents have good family’s support as many as 51 old people (89,5%), the old people independence level which is classified as independence are 33 old people (57,9%), and the old people who have good selves concept are 55 old people (96,5%). There is relationship between family’s support and the old people selves concept and there isn’t relationship between the old people independence and the old people selves concept in Bambankerep sub district  Ngaliyan District Semarang city. Family gives support to the old people especially the instrumental support so that the old people have good selves concept.Key Words; Family’s support, the old people independence, the old people selves concept